Pengaruh Supervisi Pimpinan, Fasilitas, dan Aktualisasi Diri terhadap Produktivitas Kerja Tenaga Kesehatan di RSUD Kuala Kurun, Kalimantan Tengah - Ika Nathalia; Acep Rohendi; Kahar Mulyani (BADAN PENERBIT STIEPARI PRESS, 2025)
The work productivity of healthcare workers at RSUD Kuala Kurun still faces challenges, as reflected in suboptimal service indicators and low overall productivity levels. Leadership supervision, facilities, and self-actualization are considered key factors in enhancing employee performance. This study aims to analyze the influence of leadership supervision, facilities, and self-actualization on the work productivity of healthcare workers, both partially and simultaneously. A quantitative method was employed, involving a survey of 30 healthcare workers. Data were analyzed using multiple linear regression. The results show that, partially, leadership supervision, facilities, and self-actualization have a significant positive effect on work productivity. Simultaneously, the three variables contribute significantly to the variance in productivity. The findings suggest that improving leadership supervision, providing adequate facilities, and fostering self-actualization can enhance the work productivity of healthcare workers at RSUD Kuala Kurun.